Enhancement of the performance surface roughness of wire cutting process by additives nano [AL2o3] - Sapit, Azwan; Shather, Saad Kariem; Abed, Farook Nehad (2020)
Experimental investigation and optimization of machining parameters in Wire EDM in terms adding particles Nano-reinforced titanium alloy composite abstracts among the various mechanical processes, the process of manufacturing in wire electrical discharge machines WIRE EDM is one of the most effective and costefficient manufacturing processes in the manufacture of titanium alloys Ti-6242. Ti has been dealt with in this article investigate each of operating parameters such as pulse on time, pulse off time, voltage and current insulating liquid with Nano powder [AL2O3] in WIRE EDM compounds titanium alloy. Experiments on titanium alloy carried out with powder mixture with particles size average of [5 nm]. Operating parameters such as voltage, pulse on time and pulse off time are taking into consideration four factors based on the response surface methodology. The performance of thesis evaluated WIRE EDM for ti-6242 using the surface roughness factor SURFACE ROUGHNESS. Quadratic models were developed between parameters and WIRE EDM responses by regression analysis is. The derived mathematical models are then optimized using Box-Behnken optimization based on desire analysis. The search indicates that the expected values of the model obtained to match the experimental values. Improvement in surface roughness is observed in terms of the values obtained from the Box-Behnken analysis.